Contemporary Approaches to Adaptation in Theatre (Adaptation in Theatre and Performance, 2018)
'The focus on theatre in many variant forms and contexts in Contemporary Approaches to Adaptation is both fresh and energising. The astutely organised material gives us insight into the creative and collaborative process and serves as critical provocation. In the process of this volume we see adaptation at the heart of the devising, rehearsal and performance contexts and we engage with an impressively wide-ranging, and indeed global, group of theatre directors, companies and audiences in the process. Exploratory and experimental but always political and ethical in its stance on adaptation as a collective labour, this volume provides new frameworks for debate and practice in adaptation studies.' - Julie Sanders, Pro-Vice-Chancellor, Newcastle University, UK 'Kara Reilly's carefully crafted and thought-provoking book is a welcome addition to the debate on stage adaptations. The volume captures a wide variety of theatrical and scholarly approaches and is set to become a must-read in the field.' - Margherita Laera, Lecturer in Drama and Theatre, University of Kent, UK This book examines contemporary approaches to adaptation in theatre through seventeen international case studies. It explores company and directorial approaches to adaptation through analysis of the work of Kneehigh, Mabou Mines, Robert Le Page and Katie Mitchell. It then moves on to look at the transformation of the novel onto the stage in the work of Mitchell, and in The Red Badge of Courage, The Kite Runner, Anne Frank, and Fanny Hill. Next, it examines contemporary radical adaptations of Trojan Women and The Iliad. Finally, it looks at five different approaches to postmodern metatheatrical adaptation in early modern texts of Hamlet, The Changeling, and Faustus, as well as the work of the Neo-Futurists, and the mash-up Medea/Macbeth/Cinderella. Overall, this comprehensive study offers insights into key productions, ideas about approaches to adaptation, and current debates on fidelity, postmodernism and remediation.